280 Both tumor intrinsic and extrinsic factors contribute to TIL resistance in lung cancer patients. (9th November 2020) - Wang, Chao; Teer, Jamie; Yao, Jiqiang; Anadon, Carmen; Noyes, David; Landin, Ana; Yu, Xiaoqing; Du, Dongliang; Thompson, Zachary; Fang, Bin; Koomen, John; Kim, Sungjune; et al.
Abstract : Background: Although cancer immunotherapies have achieved great success, many patients either do not respond or initially respond but later relapse. Several resistance mechanisms have been proposed from trials using immune checkpoint inhibitors or CAR-T therapy, 1, 2 but few studies have been conducted on resistance mechanisms to TIL therapy. In our trial, anti-PD1 refractory lung cancer patients were treated using TIL therapy. Several patients responded while others did not. We hypothesize that both tumor intrinsic and extrinsic factors may contribute to TIL resistance in lung cancer patients. Methods: We performed whole exome sequencing on resected baseline tumors and predicted neoantigens using the netMHCpan algorithm. Neoantigen-reactive TIL were screened using IFN-gamma ELISpot assays in a T-DC-neoantigen co-culture system. We also did the same co-culture for TCRVβ sequencing to identify neoantigen-specific TCR clonotypes. 3 Therefore, we have been able to track tumor antigen-specific T cells over time. Combined with single cell RNA sequencing & TCR sequencing, functional features of neoantigen-specific T cells in both baseline and progressive disease (PD) tumors were analyzed. Results: Our data show that the presence of neoantigen-specific TIL is associated with durable TIL benefit (p=0.031). We also identified tumor antigen-specific TCR clonotypes for 3 TIL-treated patients and followed these cells longitudinally in PBMCs. We found that although neoantigen-specific T cells had a dramatic increase after TIL infusion, patients with durable TIL benefit had a longer TIL persistence (p=0.048, figure 1). RNA sequencing on baseline tumors showed that in patients with no durable TIL benefit, genes contributing to extracellular matrix formation were highly expressed, preventing infused TILs from migrating into tumor sites. 4 In 2 TIL-treated patients, we found that neoantigens which were recognized by infused TILs were missing in PD tumors. In one patient, further investigation of TRM cells from both baseline and PD tumors showed that although T cells in the PD tumor can recognize PD tumor antigens, the T cells highly expressed PD-1, CTLA-4, Lag3 and TIGIT (figure 2), indicating an inability to control tumor progression. Enumeration of immunocyte compositions using CIBERSORT showed that higher M1/M2 ratios were found in patients with durable TIL benefit. Conclusions: In summary, higher expression of tumor antigens, longer TIL persistence and more M1 macrophages are associated with durable TIL benefit, while lack of tumor antigens, expression of immune checkpoint molecules, and upregulated formation of extracellular matrix may cause TIL resistance. Therefore, both tumor intrinsic factors and extrinsic factors contribute to TIL resistance in lung cancer patients. Acknowledgements: This work has been supported in part by the Molecular Genomics Core, Tissue Core, Proteomics Core and Flow Cytometry Core at the H. Lee Moffitt Cancer Center & Research Institute, a comprehensive cancer center designated by the National Cancer Institute and funded in part by Moffitt's Cancer Center Support Grant (P30-CA076292). This work has been funded by SU2C grant. Trial Registration: NCT03215810 Ethics Approval: The study was approved by Chesapeake IRB, approval number Pro00021984. References: Sharma P, Hu-Lieskovan S, Wargo JA & Ribas A. primary, adaptive, and acquired resistance to cancer immunotherapy. Cell 2017;168:707–723, doi:10.1016/j.cell.2017.01.017 Tseng D, Padda SK & Wakelee HA. Perspectives on acquired resistance to PD-1 Axis inhibitors in patients with non-small cell lung cancer. J Thorac Oncol 2018;13:741–744, doi:10.1016/j.jtho.2018.04.008. Danilova, L. et al. The mutation-associated neoantigen functional expansion of specific T Cells (MANAFEST) Assay: A sensitive platform for monitoring antitumor immunity. Cancer Immunol Res 6;888–899, doi:10.1158/2326-6066.CIR-18-0129 ( 2018). Caruana I, et al. Heparanase promotes tumor infiltration and antitumor activity of CAR-redirected T lymphocytes. Nat Med 2015;21:524–529doi:10.1038/nm.3833.